2020
DOI: 10.1016/j.medidd.2020.100046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Shock Protein 90 Inhibition In the Lungs

Abstract: Inhibition of Hsp90 is associated with anti-inflammatory effects. We employed human lung microvascular endothelial cells to investigate the effects of the Hsp90 inhibitors 17-AAG, AUY-922 and 17-DMAG in the unfolded protein response (UPR) and viability of lung cells. Our observations indicate that moderate doses of those compounds trigger the activation of the UPR without inducing lethal effects in vitro . Indeed, AUY-922 triggered UPR activation in the lungs of C57BL/6 mice. UPR has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…UPR directly regulates the expression levels of P53 in the lung endothelium [ 60 ]. Recent studies suggested that the endothelial barrier enhancing effects of Hsp90 inhibitors and growth hormone-releasing hormone (GHRH) antagonists might be associated with UPR mediated P53 expression [ [69] , [70] , [71] ]. GHRH antagonist induces the expression of P53 and suppresses the major inflammatory extracellular signal-regulated kinases 1/2 (ERK1/2), Janus kinase 2 (JAK2), and signal transducer and activator of transcription 3 (STAT3) pathways in lung microvascular endothelial cells which express GHRH receptors [ 37 ].…”
Section: Human Pulmonary Vasculaturementioning
confidence: 99%
“…UPR directly regulates the expression levels of P53 in the lung endothelium [ 60 ]. Recent studies suggested that the endothelial barrier enhancing effects of Hsp90 inhibitors and growth hormone-releasing hormone (GHRH) antagonists might be associated with UPR mediated P53 expression [ [69] , [70] , [71] ]. GHRH antagonist induces the expression of P53 and suppresses the major inflammatory extracellular signal-regulated kinases 1/2 (ERK1/2), Janus kinase 2 (JAK2), and signal transducer and activator of transcription 3 (STAT3) pathways in lung microvascular endothelial cells which express GHRH receptors [ 37 ].…”
Section: Human Pulmonary Vasculaturementioning
confidence: 99%
“…Bovine pulmonary artery endothelial cells treated with this mannosidase inhibitor exerted hyper-permeability responses [6] . Heat shock protein 90 (Hsp90) inhibitors are UPR inducers [ 7 , 8 ] . It was recently reported that Luminespib (AUY-922), an advanced Hsp90 inhibitor, counteracts the Kifunensine-Induced lung endothelial barrier dysfunction [ 9 ].…”
Section: Unfolded Protein Response (Upr)mentioning
confidence: 99%
“… 1 P53 protects the endothelium cells against the lipopolysaccharide (LPS)-induced endothelial hyperpermeability by reducing the generation of the reactive oxygen species, 2 by suppressing the inflammatory RhoA/MLC2 pathway, 3 and by inducing the repairing activities of the unfolded protein response in the lungs. 4 5 …”
Section: Figmentioning
confidence: 99%
“…1 P53 protects the endothelium cells against the lipopolysaccharide (LPS)-induced endothelial hyperpermeability by reducing the generation of the reactive oxygen species, 2 by suppressing the inflammatory RhoA/MLC2 pathway, 3 and by inducing the repairing activities of the unfolded protein response in the lungs. 4,5 Lung endothelial barrier dysfunction is both a cause and a consequence of severe lung inflammatory disease, including Fig. 1 (A-F) Western blot analysis of phosphorylated P53 (pP53 ser392 , pP53 ser46 , pP53 ser15 , pP53 ser33 ) and total P53 expression after treatment of bovine pulmonary artery endothelial cell (BPAEC) with either lipoteichoic acid (LTA) (10 µg/mL) or vehicle (VEH) (phosphate-buffered saline [PBS]) for 2, 4, and 6 hours.…”
mentioning
confidence: 99%